The impact of early use of statin in sepsis patients with acute kidney injury: a study based on MIMIC-IV - Zhan, Xiaona; Huang, Haifeng; Ye, Ling; Zhu, Shenglang; Chen, Jiehui (Frontiers in Pharmacology, 2025)
ObjectiveSepsis-associated acute kidney injury (SA-AKI) is a prevalent and serious condition in the ICU. The efficacy of statin in these patients remains unclear. The purpose of this study was to investigate the impact of the early use of statin on the prognosis of SA-AKI patients.MethodsThe patients included in this study were derived from the MIMIC-IV database. Patients were divided into the non-statin and statin groups based on whether they received statin within 48 h of admission. After propensity score matching, time-dependent Cox regression analysis was used to evaluate the relationship between the early use of statin and mortality. The relationship between treatment and the recovery of renal function was assessed by logistic analysis, and the association between the use of statin and length of ICU stay was evaluated by the negative binomial regression model.ResultsA total of 11,667 patients were included in the study. After propensity score matching, there were 1,585 patients in each group, and the baselines between the two groups were comparable. Although statin use was associated with prolonged ICU stay, it was significantly linked to reduced 28-day and 90-day mortality and improved renal function recovery. Subgroup analysis indicated that the protective effect of early statin use was more effective in patients with hypertension. In comparison with the non-statin group, the use of different types of statin were associated with reduced 28-day mortality in sepsis patients with AKI. Compared with the rosuvastatin group, there was no significant difference in reducing the risk of mortality among other types of statins.ConclusionIn sepsis patients with AKI, the early use of statin was associated with a reduction in 28-day and 90-day mortality. The early use of statin plays a protective role in patients with SA-AKI.